Involvement of Transcription Factor FoxO1 in the Pathogenesis of Polycystic Ovary Syndrome - Xu, Renfeng; Wang, Zhengchao (Frontiers in Physiology, 2021)
FoxO1 is a member of the forkhead transcription factor family subgroup O (FoxO), which is expressed in many cell types, and participates in various pathophysiological processes, including cell proliferation, apoptosis, autophagy, metabolism, inflammatory response, cytokine expression, immune differentiation, and oxidative stress resistance. Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in the women of childbearing age, which is regulated via a variety of signaling pathways. Currently, the specific mechanism underlying the pathogenesis of PCOS is still unclear. As an important transcription factor, FoxO1 activity might be involved in the pathophysiology of PCOS. PCOS has been associated with insulin resistance and low-grade inflammatory response. Therefore, the studies regarding the role of FoxO1 in the incidence and associated complications of PCOS will help provide novel ideas for establishing the treatment strategy of PCOS.